Buffer-Capacity-Based Livelihood Resilience to Stressors—An Early Warning Tool and Its Application in Makueni County, Kenya - Matter, Selina; Boillat, Sébastien; Ifejika Speranza, Chinwe (Frontiers in Sustainable Food Systems, 2021)
Persistent vulnerability of smallholder farmers to natural hazards and livelihood insecurity call for the identification of measures that enhance the resilience of their agriculture-dependent livelihoods. Without understanding how to secure smallholder livelihoods against adverse social-ecological dynamics, especially related to climate variability and market failures, hunger, poverty and livelihood collapse are likely to become more entrenched. This study aims for this better understanding by applying the Livelihood Resilience Indicator Framework to investigate the livelihood resilience of smallholder farmers in Makueni County, Kenya, to disease and pest infestations, low yields, and hunger. We analyzed the buffer capacity dimension of resilience among smallholder farmers, using survey data collected in 2016 on 134 households. We conducted principal component analysis to calculate a buffer capacity index at household level, which we then assessed in relation to crop and livestock pests and diseases, yields and food shortage. We found that there was a significant positive correlation between buffer capacity and maize yields, which could be attributed to diversity in agricultural practices and income. The incidence of pests and diseases correlated significantly and negatively with buffer capacity and specifically with land size, economic status, and social capital. While no significant relationship could be established between buffer capacity and the occurrence of food insecurity, this variable correlated with access to land and livestock, diversity in agricultural practices and access to infrastructure. The expected positive relation between food security and access to infrastructure and services turned out to be negative, raising questions about the relations between the livelihood resilience construct and rural infrastructure and services. More differentiation is thus needed on the multi-faceted interactions between access to infrastructure and services, including their actual use and benefits to livelihood resilience. In general, most findings supported the Livelihood Resilience Indicator Framework in that households with higher buffer capacity were better equipped to cope with shocks and stressors, hence demonstrating the potential of the framework as an early warning tool.